2022
DOI: 10.1002/rth2.12806
|View full text |Cite
|
Sign up to set email alerts
|

Stability of specimens for use in the Centers for Disease Control and Prevention assays for factor VIII and IX inhibitors

Abstract: The Centers for Disease Control and Prevention (CDC) Nijmegen-Bethesda Assay (NBA) 1 is a modification of traditional methods 2,3 for measurement of factor VIII (FVIII) and factor IX (FIX) inhibitors that includes a 30-minute preanalytical heat treatment (PHT) step to remove endogenous and infused FVIII or FIX. Specimens for inhibitor tests using PHT thus do not require the stringent conditions needed to maintain clotting factors during shipping and storage, as we have previously documented by split-sample ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A recent study has demonstrated that both FVIII and FIX inhibitor positive sample can be stored at room temperature for 1 week, while stored at À70 C inhibitor positive samples can be stored for up to 15 years after their original analyses. 55 For FVIII:C and FIX:C it has been demonstrated that clotting activity should be measured within 2 and 4 h, respectively. 56 Storage of frozen plasma at À70 C for the measurement of FVIII:C and FIX:C is possible for 18 and 24 months, respectively.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has demonstrated that both FVIII and FIX inhibitor positive sample can be stored at room temperature for 1 week, while stored at À70 C inhibitor positive samples can be stored for up to 15 years after their original analyses. 55 For FVIII:C and FIX:C it has been demonstrated that clotting activity should be measured within 2 and 4 h, respectively. 56 Storage of frozen plasma at À70 C for the measurement of FVIII:C and FIX:C is possible for 18 and 24 months, respectively.…”
Section: Generalmentioning
confidence: 99%
“…Standard centrifugation conditions for blood coagulation samples can be used (15 min at 1500× g ). A recent study has demonstrated that both FVIII and FIX inhibitor positive sample can be stored at room temperature for 1 week, while stored at −70°C inhibitor positive samples can be stored for up to 15 years after their original analyses 55 . For FVIII:C and FIX:C it has been demonstrated that clotting activity should be measured within 2 and 4 h, respectively 56 .…”
Section: Introductionmentioning
confidence: 99%